Multi-criteria ranking of organizational factors affecting the learning quality outcomes in elementary education in Serbia - Epifanić, Vladislava; Urošević, Snežana; Dobrosavljević, Andrea; Kokeza, Gordana; Radivojević, Nikola (Journal of Business Economics and Management, 2021)
The research within this paper is motivated by the opinion that different organizational factors in primary education can have a stronger or weaker impact on the quality of the learning outcome. Organizational factors, criteria analyzed in this paper, are school management, school infrastructure, students’ foreknowledge, teacher competencies, curriculum content, student motivation, and the quality of the teaching process. Using SWARA (Step-wise Weight Assessment Ratio Analysis) method of multi-criteria decision-making, the answers of elementary school principals, members of the panel of experts, were processed. The calculation within this method was performed using fuzzy numbers to ensure the reliability of expert evaluations. The results of the applied method, in the form of weighting coefficients of the criteria, indicate that school management has an influence on the selection and building of teachers’ competencies while the given competence can indirectly affect the overall success of students through the establishment of an adequate school infrastructure, which affects the knowledge quality. Knowing the factor that has the highest impact enables principals to manage this factor and contribute to enhancing the knowledge quality. This research contributes to raising awareness of the importance of particular organizational factors in elementary education and the need to improve them. First published online 28 October 2020